2012
DOI: 10.2139/ssrn.2141297
|View full text |Cite
|
Sign up to set email alerts
|

Whistleblowing and Compliance in the Judicial Hierarchy

Abstract: One way that principals can overcome the problem of informational asymmetries in hierarchical organizations is to enable whistleblowing. We evaluate how whistleblowing influences compliance in the judicial hierarchy. We present a formal model in which a potential whistleblower may, at some cost, signal noncompliance by a lower court to a higher court. A key insight of the model is that whistleblowing is most informative when it is rare. While the presence of a whistleblower can increase compliance by lower cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…Existing theories have demonstrated that a lower court's private information about a case's facts creates an incentive for an upper court to defer (e.g., Beim 2017;Beim, Hirsch, and Kastellec 2014;Cameron, Segal, and Songer 2000;Carrubba and Clark 2012;Clark and Carrubba 2012;Lax 2012). However, the particular way that fact finding is conceptualized (and therefore modeled) matters for understanding both the scope and form of this deference (see Stephenson 2011).…”
Section: Fact Finding In the Judicial Hierarchymentioning
confidence: 99%
See 1 more Smart Citation
“…Existing theories have demonstrated that a lower court's private information about a case's facts creates an incentive for an upper court to defer (e.g., Beim 2017;Beim, Hirsch, and Kastellec 2014;Cameron, Segal, and Songer 2000;Carrubba and Clark 2012;Clark and Carrubba 2012;Lax 2012). However, the particular way that fact finding is conceptualized (and therefore modeled) matters for understanding both the scope and form of this deference (see Stephenson 2011).…”
Section: Fact Finding In the Judicial Hierarchymentioning
confidence: 99%
“…Second, this article adds to recent models focused on the role of opinion writing in managing hierarchical relationships between courts, and between courts and legislatures (e.g., Beim, Hirsch, and Kastellec 2014;Clark and Carrubba 2012;Staton and Vanberg 2008). Clark and Carrubba (2012) conceive of opinions as consisting of legal rules and persuasive quality.…”
Section: Fact Finding In the Judicial Hierarchymentioning
confidence: 99%
“…More recently, Ting (2008) shows that the informational advantages of whistle-blowing might be outweighed by the costs of employees exerting less effort. In a related paper, Beim et al (2014) show that too much whistle-blowing decreases the informativeness of such disclosure and might yield more wrongdoing in the first place. Relatedly, Austen-Smith and Feddersen (2009) analyze the managerial choice of whistleblowing practises for providing incentives to report violations and committing to fix such violations internally when they are privately reported.…”
Section: Related Literaturementioning
confidence: 95%
“…Although dissenting opinions at the Supreme Court have become more common (Corley et al 2013), unanimity is a powerful norm at the U.S. Courts of Appeals (Cross 2007;Kim 2009). Dissenters are argued to be whistleblowers in the federal judicial hierarchy, signaling potential deviation from Supreme Court or circuit precedent or procedure (Beim et al 2014a;Blackstone & Collins 2014;Cross & Tiller 1998;Hazelton et al 2016). The presence of a dissent has long been thought to be a factor in decisions on certiorari (Tanenhaus et al 1963;Ulmer et al 1972).…”
Section: Separate Opinion Writing In the Federal Courtsmentioning
confidence: 99%